2013
DOI: 10.1152/ajplung.00123.2013
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-1 and caveolae form the mechanosensing complex necessary for NOX2 activation and angiogenic signaling with stopped flow in pulmonary endothelium

Abstract: AB, Chatterjee S. PECAM-1 and caveolae form the mechanosensing complex necessary for NOX2 activation and angiogenic signaling with stopped flow in pulmonary endothelium. Am J Physiol Lung Cell Mol Physiol 305: L805-L818, 2013. First published September 27, 2013 doi:10.1152/ajplung.00123.2013.-We showed that stop of flow triggers a mechanosignaling cascade that leads to the generation of reactive oxygen species (ROS); however, a mechanosensor coupled to the cytoskeleton that could potentially transduce flow st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 54 publications
(85 reference statements)
1
66
0
Order By: Relevance
“…Interestingly, both PECAM-1 and glypican-1 have been independently shown to be expressed in caveolin-1-containing membrane fractions (43,44), with the latter believed to be involved in shear-induced NO production through a glypican-caveolae-endothelial nitric-oxide synthase mechanism (45). Additionally, it has been recently reported that PECAM-1 and caveolin-1 form a mechanosensing complex that is necessary for NAPDH oxide 2 (NOX2) and angiogenic signaling in pulmonary endothelial cells in response to abrupt cessation of flow (44). Therefore, it is not inconceivable that a subset of PECAM-1 forms a functionally distinct mechanosensitive caveolar complex together with glypican-1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both PECAM-1 and glypican-1 have been independently shown to be expressed in caveolin-1-containing membrane fractions (43,44), with the latter believed to be involved in shear-induced NO production through a glypican-caveolae-endothelial nitric-oxide synthase mechanism (45). Additionally, it has been recently reported that PECAM-1 and caveolin-1 form a mechanosensing complex that is necessary for NAPDH oxide 2 (NOX2) and angiogenic signaling in pulmonary endothelial cells in response to abrupt cessation of flow (44). Therefore, it is not inconceivable that a subset of PECAM-1 forms a functionally distinct mechanosensitive caveolar complex together with glypican-1.…”
Section: Discussionmentioning
confidence: 99%
“…After extensive further study, we found that the source of ROS with ischemia was the endothelium, and the mechanism was related to altered mechanotransduction, namely the cessation of the normal shear forces applied to the pulmonary endothelial cells by the pulmonary blood flow (3,71,75). Additional studies showed that shear in pulmonary endothelium is sensed by caveolae and is somehow related to endothelial platelet-endothelial adhesion molecule (PECAM) (61,63 pulmonary endothelial ATP-sensitive K ϩ channels in the open configuration, contributing to the endothelial cell transmembrane potential; cessation of flow leads to ATP-sensitive K ϩ channel closure, endothelial cell membrane depolarization, and activation of NOX2 with subsequent O 2 ·Ϫ generation (4,14,16) (Fig. 3).…”
Section: Lung Ischemiamentioning
confidence: 99%
“…In this context, platelet EC adhesion molecule-1, a mechanosensitive membrane protein that is upregulated during inflammation, 87 may mediate not only NOX2-derived superoxide generation in response to disturbed FSS 88 but also glycogen synthase kinase-3β activation 89 leading to enhanced EC oxidative stress because of diminished Nrf2 activity. BTB and CNC homology 1 (Bach-1) is a Nrf2-regulated transcriptional repressor of a subset of ARE-regulated genes such as HO-1 39 and thus antagonizes the activator function of Nrf2.…”
Section: Hypertensionmentioning
confidence: 99%